Gate work function variability-dependent short channel effects in nanoscale double gate finFETs: an in-depth comparative analysis - Nura Muhammad Shehu; Garba Babaji; Mutari Hajara Ali (International Journal of Engineering and Technology, 2023)
We explored the impact of gate work-function variations on Short Channel Effects (SCEs) in nanoscale Double Gate FinFETs utilizing GaAs, GaSb, GaN, and Si as semiconductor channel materials. The analysis is carried out using PADRE Simulator. Critical performance parameters examined are Drain Induced Barrier Lowering (DIBL), Subthreshold Swing (SS), Threshold Voltage Roll-off, On-Current and Transconductance. The results show that GaAs-FinFET excels in terms of DIBL and threshold voltage and on-current. GaN-FinFET shows higher superiority in terms of SS. While GaAs and GaN outperform the other two in terms of transconductance. These findings underscore the significance of work-function variability in enhancing nanoscale electronic device performance and developing semiconductor technology.